Food poisoning due to a TSST1-producing Staphylococcus aureus. (2021) - Goudsmit, Anouk; Markowicz, Samuel; Lali, Salah Eddine; Cherifi, Soraya
Abstract: Toxic Shock Syndrome (TSS) is a very rare and severe complication of Staphylococcus aureus infections. However, bacteremia is very uncommon in this disease. We present here the case of a healthy 15-year old boy who presented septic shock and diffuse exanthema four hours after eating in a fast food restaurant. Blood cultures were positive for a TSST-1 producing Staphylococcus aureus . The patient was treated with antibiotics and fully recovered.